Thixotropic Supramolecular Pectin-Poly(Ethylene Glycol) Methacrylate (PEGMA) Hydrogels - Chan, Siew Yin (Polymers (Basel), 2016)
Pectin is an anionic, water-soluble polymer predominantly consisting of covalently 1,4-linked α-d-galacturonic acid units. This naturally occurring, renewable and biodegradable polymer is underutilized in polymer science due to its insolubility in organic solvents, which renders conventional polymerization methods impractical. To circumvent this problem, cerium-initiated radical polymerization was utilized to graft methoxy-poly(ethylene glycol) methacrylate (mPEGMA) onto pectin in water. The copolymers were characterized by (1)H nuclear magnetic resonance (NMR), Fourier transform infrared (FTIR) spectroscopy and thermogravimetric analysis (TGA), and used in the formation of supramolecular hydrogels through the addition of α-cyclodextrin (α-CD) to induce crosslinking. These hydrogels possessed thixotropic properties; shear-thinning to liquid upon agitation but settling into gels at rest. In contrast to most of the other hydrogels produced through the use of poly(ethylene glycol) (PEG)-grafted polymers, the pectin-PEGMA/α-CD hydrogels were unaffected by temperature changes.